2015
DOI: 10.5604/20831862.1150304
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of graduated compression stockings on cardiorespiratory performance

Abstract: The use of graduated compression stockings (GCS) in sport has been increasing in the last years due to their potential positive effects for athletes. However, there is little evidence to support whether these types of garments actually improve cardiorespiratory performance. The aim of this study was to examine the cardiorespiratory responses of GCS during running after three weeks of regular use. Twenty recreational runners performed three tests on different days: test 1) – a 5-min maximal effort run in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
(53 reference statements)
3
6
0
Order By: Relevance
“…As expected, HR increased as a function of time (cardiac drift) but we did not find any difference across garment conditions. This result is similar to those of previous studies during (Ali et al, 2007 ; Duffield and Portus, 2007 ; Sperlich et al, 2011 ; Wahl et al, 2011 ; Vercruyssen et al, 2012 ; Born et al, 2014 ; Priego Quesada et al, 2015 ) or after exercise (Duffield et al, 2010 ; Ménétrier et al, 2011 ). On the contrary, a beneficial effect of wearing CS was found in muscle oxygenation during all resting situations, including after the test, which was likely due to an increased perfusion and reduced venous pooling in CS, as previously shown (Bochmann et al, 2005 ; Bringard et al, 2006 ; Ménétrier et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, HR increased as a function of time (cardiac drift) but we did not find any difference across garment conditions. This result is similar to those of previous studies during (Ali et al, 2007 ; Duffield and Portus, 2007 ; Sperlich et al, 2011 ; Wahl et al, 2011 ; Vercruyssen et al, 2012 ; Born et al, 2014 ; Priego Quesada et al, 2015 ) or after exercise (Duffield et al, 2010 ; Ménétrier et al, 2011 ). On the contrary, a beneficial effect of wearing CS was found in muscle oxygenation during all resting situations, including after the test, which was likely due to an increased perfusion and reduced venous pooling in CS, as previously shown (Bochmann et al, 2005 ; Bringard et al, 2006 ; Ménétrier et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
“…Positive effects in performance have also been noted in incremental tests (Kemmler et al, 2009 ; Sear et al, 2010 ), repeated sprinting (Higgins et al, 2009 ; Born et al, 2014 ), and jumping height following submaximal exercise (Rugg and Sternlicht, 2013 ; Bieuzen et al, 2014 ) or after a 10 km run (Ali et al, 2011 ). Conversely, other studies have reported no measurable effect on limb volume (Areces et al, 2015 ), fractional oxygen utilization (Kemmler et al, 2009 ; Wahl et al, 2011 ; Born et al, 2014 ; Priego Quesada et al, 2015 ; Stickford et al, 2015 ), muscle oxygenation or blood flow (Vercruyssen et al, 2012 ; Born et al, 2014 ), heart rate or indicators of central cardiovascular adaptations (Ali et al, 2007 ; Sperlich et al, 2011 ; Wahl et al, 2011 ; Vercruyssen et al, 2012 ; Born et al, 2014 ; Priego Quesada et al, 2015 ), lactate or exercise metabolite removal (Kemmler et al, 2009 ; Ali et al, 2010 ; Sperlich et al, 2011 ; Wahl et al, 2011 ; Vercruyssen et al, 2012 ; Areces et al, 2015 ), ratings of perceived exertion (RPE) or DOMS (Ali et al, 2007 , 2010 ; Bovenschen et al, 2013 ; Areces et al, 2015 ; Priego Quesada et al, 2015 ), running economy and gait kinematics (Varela-Sanz et al, 2011 ; Stickford et al, 2015 ; Vercruyssen et al, 2016 ), maximal voluntary and evoked contractions (Vercruyssen et al, 2016 ), as well as performance in repeated sprinting (Duffield et al, 2008 ), or in running performed at maximal (Ali et al, 2007 ; Priego Quesada et al, 2015 ) and at sub-maximal exercise intensities (Ali et al, 2007 , 2011 ; Wahl et al, 2011 ; Vercruyssen et al, 2012 ; Priego Quesada et al, 2015 ). This abundant but heterogeneous literature may underline probable task-dependent ergogenic effects of the compression when used during exercise.…”
Section: Introductionmentioning
confidence: 93%
“…However, no difference in heart rate and perception of fatigue was observed in the present study between conditions. Taking into account that previous studies have observed no differences in cardiovascular performance as a result of the use of GCS during running (Ali et al, 2010;Kemmler et al, 2009;Priego Quesada et al, 2015b;Sperlich et al, 2010), it is likely that muscle fatigue was similar when running with and without GCS and therefore it may not be responsible for the different temperatures observed in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…Finally, regarding the use of compression stockings, 10 protocols performed endurance tests [3948], 3 combined tests of different types (endurance and strength [49], and endurance and speed [50,51]), and two strength tests [52,53]. The use of compression stockings did not significantly improve heart rate [41,4648,51], respiratory parameters with an emphasis on oxygen consumption [41,42,46,48], skin temperature [47], plasma markers of muscle damage [39], blood lactate concentration [41,51], one-leg hop parameters [53], or blood flow and muscle oxygenation [41,42]. Neither were there significant improvements found in performance parameters: the time to exhaustion remained unchanged in the group with compression stockings compared to the control group [48], the partial times of each of the 400 m sets did not show any notable change [51], and the pace and total race time in an official marathon were unaffected [39].…”
Section: Resultsmentioning
confidence: 99%
“…Neither were there significant improvements found in performance parameters: the time to exhaustion remained unchanged in the group with compression stockings compared to the control group [48], the partial times of each of the 400 m sets did not show any notable change [51], and the pace and total race time in an official marathon were unaffected [39]. But the use of compression stockings significantly improved attenuation and impact [43], muscle potential [42], blood lactate concentration [4248], leg volume [50], counter-movement jump parameters [49], and muscle oxygenation [52]. Two studies [44,45] performed nuclear magnetic resonance imaging to analyse muscle cross section (T2).…”
Section: Resultsmentioning
confidence: 99%